Correlation of mutagenesis level with expression of reparative enzyme O6-methylguanine DNA methyltransferase during establishment of cell lines in vitro - Macewicz, L.L.; Kushniruk, V.O.; Iatsyshyna, A.P.; Kotsarenko, K.V.; Lylo, V.V.; Akopyan, G.R.; Huleuk, N.L.; Mykytenko, D.O.; Lukash, L.L. (Вiopolymers and Cell, 2013)
Long-term cultivation of cell lines inevitably leads to genetic and epigenetic changes. The aim of this work was a comparative analysis of karyotype and level of the expression of reparative enzyme O6-methylguanine-DNA- methyltransferase (MGMT) at different stages of establishment and stabilization of human cell line 4BL and cell line of mouse germ cells G1. Methods. The set of methods was used to research the dynamics of karyotypes changes: the differential staining of chromosomes, FISH-method and comparative genomic hybridization. The level of MGMT expression was analyzed by PCR reaction and Western blot analysis. Results. General trends of establishment of mouse and human cell lines were revealed: at the first stage, which is characterized by increased structural instability of the genome, an increase in the MGMT expression was revealed while at the second stage of stabilization – a decrease in the expression. Therefore, almost complete disappearance of MGMT protein in unmodified form (24 kDa) is observed. Conclusions. Statistically significant correlation between MGMT repair enzyme and mutations induction processes during mammalian cell adaptation and cell line establishment to in vitro was described. Тривале культивування клітинних ліній неминуче призводить до виникнення генетичних та епігенетичних змін. Мета. Порівняльний аналіз каріотипу і рівня експресії репаративного ферменту О6-метилгуанін-ДНК метилтрансферази (MGMT) на різних етапах становлення та стабілізації клітинної лінії людини 4BL і лінії ембріональних гермінативних клітин миші G1. Методи. Зміни каріотипу в динаміці досліджували, використовуючи диференційне забарвлення хромосом, FISH-метод і порівняльну геномну гібридизацію. Ген MGMT та його експресію вивчали за допомогою ПЛР та Вестерн-блот аналізу. Результати. Період становлення ліній клітин миші та ліній клітин людини має загальні тенденції: на першому етапі, який характеризується підвищеною структурною нестабільністю геному, виявлено зростання рівня експресії гена MGMT, а на другому – етапі стабілізації – зниження рівня експресії даного гена. При цьому спостерігали практично повну відсутність немодифікованої форми білка MGMT (24 кДа). Висновки. Встановлено достовірну позитивну кореляцію рівня експресії репаративного ферменту MGMT з мутаційними процесами, які виникають при адаптації клітин до умов культивування у період становлення ліній клітин ссавців. Длительное культивирование клеточных линий неизбежно приводит к возникновению генетических и эпигенетических изменений. Цель Cравнительный анализ кариотипов и уровня экспрессии репаративного фермента MGMT на разных стадиях становления и стабилизации клеточной линии человека 4BL и линии эмбриональных герминативных клеток мыши G1. Методы. Исследовали изменение кариотипа в динамике с использованием дифференциальной окраски хромосом, FISH-метода и сравнительной геномной гибридизации. Ген MGMT и его экспрессию изучали с помощью ПЛР и Вестерн-блот-анализа. Результаты. Период становления клеточных линий человека и мыши характеризуется общими тенденциями: на первом этапе, где наблюдается повышенная структурная нестабильность генома, выявлено возрастание уровня экспрессии гена MGMT, а на втором – этапе стабилизации – снижение уровня экспрессии указанного гена. При этом отмечено практически полное отсутствие немодифицированной формы белка MGMT (24 кДа). Выводы. Обнаружена достоверная позитивная корреляция уровня экспрессии репаративного фермента MGMT с мутационными процессами, возникающими при адаптации клеток к условиям культивирования в период становления клеточных линий млекопитающих.